URGENSI PEMBELAJARAN BAHASA ARAB BAGI PENGHAFAL AL-QUR’AN DI PON-PES AL-HIDAYAT GERNING - Putyara Freday, Ame; Kusuma, Nurhadi; Maisaroh, Iis (Jurnal Pendidikan Bahasa Arab L-DHAD, 2024)
Abstrak This research aims to determine the urgency of learning Arabic. In this research the author used a qualitative approach, with descriptive analysis methods. In this case the author describes the urgency of learning Arabic for students who memorize the Koran at the Al-Hidayat Gerning Islamic boarding school. The results of the research that the author has conducted show the importance of learning Arabic for memorizing the Qur'an. This is proven by the many benefits felt by memorizers of the Qur'an, especially in the memorization process. So it can be concluded that there is a correlation between learning Arabic and memorizing the Al-Qur'an, so there is an urgency or importance in learning Arabic before, during, or after memorizing the Al-Qur'an. Firstly, a Hafizh of the Qur'an really needs Arabic to help memorize and maintain his memorization, because by having the ability to speak Arabic a Hafizh will remember his memorization through the story or theme of the verse that is being memorized. Second, it can help speed up memorization and also make you understand the meaning contained in the verse. By learning Arabic, students can also apply the contents of the Koran in their daily lives. Because the real purpose of memorizing the Koran is so that you can apply its contents in everyday life. Third, learning Arabic for memorizing the Qur'an is to help memorize the characters and word structures in the verses of the Qur'an. Keywoards: Learning, Arabic, Memorize the Koran